Effect of the impact of rigid rods on coffee fruit detachment efficiency by mechanical vibrations - Queiroz Gomes, Ely; Lúcio Santos, Fabio; Nascimento, Moysés; Silveira Velloso, Nara (Coffee Science - ISSN 1984-3909, 2020)
The mechanization of field activities has been the response of coffee producers to the labor shortage, especially for fruit harvesting. The use of mechanical harvesters allows greater harvesting efficiency and ensures the economic viability of coffee plantations, which currently depend mainly on the reduction in production costs. The principle used for mechanized coffee harvesting is based on the principle of mechanical vibration. The objective of this study was to analyze the dynamic behavior of the coffee fruit-peduncle-branch system under mechanical vibration and the impact of the vibrating rods on the fruit detachment process in association with this behavior. Fragments of coffee branches containing fruits in the unripe and ripe stages were used in this experiment. These samples were subjected to different frequencies (20, 30, 40, and 50 Hz) and amplitudes (0.002, 0.003, and 0.004 m). Another variable analyzed was the form of vibration transmission to the fruits, with the vibrations being transmitted to the samples with or without the impact of the fiberglass rods. The fruit detachment efficiency increased as the ripening stage progressed from unripe to ripe. A higher detachment efficiency occurred with the increase in vibration frequency and amplitude because of the higher vibrational energy imposed on the fruit. The detachment efficiency was low when the vibration was transmitted without the impact of the rods. Conversely, the vibration in combination with impact achieved a mean detachment efficiency of approximately 90%. Key words: Coffee crop; dynamic behavior; harvester machine; mechanical harvesting.